2022
DOI: 10.1200/jco.2022.40.16_suppl.4520
|View full text |Cite
|
Sign up to set email alerts
|

RC48-ADC for metastatic urothelial carcinoma with HER2-positive: Combined analysis of RC48-C005 and RC48-C009 trials.

Abstract: 4520 Background: RC48-ADC (Disitamab Vedotin) is a novel humanized anti-HER2 antibody-drug conjugate (ADC). RC48-ADC demonstrated a promising efficacy with a manageable safety profile in HER2-positive locally advanced or metastatic UC patients who failed to platinum based chemotherapy in RC48-C005 and RC48-C009 trials. Here are the pooled results of the two studies with the supplementary efficacy, safety and updated OS data. Methods: Both of the two trials are single-arm, multi-center, phase II trials. Eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…RC48-C005 (NCT03507166) and RC48-C009 (NCT03809013) are 2 trials that evaluated RC48-ADC in 107 patients with HER-2 positive (immunohistochemistry [IHC] 2+ or 3+) UC. In a combined analysis, confirmed ORR was 50.5%, median PFS was 5.9 months, and median OS was 14.2 months 38 . Grade ≥3 TRAEs were numbness (15.0%) and neutropenia (12.1%), with no dose-limiting toxicity reported 38 .…”
Section: Existing and Emerging Targets In Ucmentioning
confidence: 94%
See 2 more Smart Citations
“…RC48-C005 (NCT03507166) and RC48-C009 (NCT03809013) are 2 trials that evaluated RC48-ADC in 107 patients with HER-2 positive (immunohistochemistry [IHC] 2+ or 3+) UC. In a combined analysis, confirmed ORR was 50.5%, median PFS was 5.9 months, and median OS was 14.2 months 38 . Grade ≥3 TRAEs were numbness (15.0%) and neutropenia (12.1%), with no dose-limiting toxicity reported 38 .…”
Section: Existing and Emerging Targets In Ucmentioning
confidence: 94%
“…38 Grade ≥3 TRAEs were numbness (15.0%) and neutropenia (12.1%), with no dose-limiting toxicity reported. 38 Furthermore, RC48-ADC has shown favorable results in HER-2-negative (IHCor 1+) patients with metastatic UC (NCT04073602). A total of 19 patients were enrolled with ORR of 26.3%.…”
Section: Her-2mentioning
confidence: 98%
See 1 more Smart Citation
“…A combined analysis of the RC48‐C005 and RC48‐C009 studies revealed that RC48‐ADC monotherapy achieved an ORR of 50.5% (95% CI: 40.6%–60.3%) in HER2‐positive (IHC2+ and 3+) mUC patients who had progressed on at least one systemic chemotherapy. The disease control rate (DCR) was 82.2% (95% CI: 73.7%, 89.0%), mPFS of 5.9 months (95% CI: 4.2, 7.2) and a median overall survival (mOS) of 14.2 months (95% CI: 9.7, 18.8) 17 . The RC48‐C011 study demonstrated that RC48‐ADC monotherapy achieved an ORR of 26.3% (95% CI: 9.1%, 51.2%) in la/mUC patients with low HER2 expression (IHC1+ and 0), a DCR of 94.7%, an mPFS of 5.5 months (95% CI: 3.9, 6.8), and an mOS of 16.4 months (95% CI: 7.1, 21.7) 16 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been trialed in a single-arm phase II study in HER2positive locally advanced or mUC patients who failed platinum-based chemotherapy. To date, RC48-ADC has shown promising efficacy with a manageable safety profile (overall response rate was 50.5% (95% CI, 40.6-60.3%) 69. …”
mentioning
confidence: 99%